Political Institutional Reforms in China from Vietnam's Perspective - Hồng, Nguyễn Thu; Cường , Nguyễn Anh; Hiếu, Đinh Tiến; Loan, Đỗ Thị Thanh (Journal of Ecohumanism, 2024)
This study aims to enhance our comprehension of significant shifts in China's political-institutional transformation process, thereby enabling a more accurate assessment of the country's internal political landscape. The primary objective of this research paper is to elucidate three fundamental aspects of the reform of political institutions in China, spanning from 1978 to the present. This inquiry seeks to address three key aspects pertaining to China's political and institutional reform. Firstly, it aims to explore the motivations behind China's pursuit of such reforms. Secondly, it seeks to identify and examine the significant political and institutional reforms implemented by China since 1978. Lastly, it aims to assess the accomplishments and constraints associated with China's ongoing political and institutional reform endeavors. Drawing upon sources from Chinese and Vietnamese researchers, the authors employ synthetic, logical, historical, and comparative analysis methodologies to comprehensively examine the landscape of China's political and institutional reform from 1978 to the present. Scholarly evidence indicates that the reform of political institutions in China is primarily aimed at solidifying and enhancing the socialist character of the regime, with the success of such reform being heavily contingent upon the actions and decisions of the leader in power.